INDONESIA'S NATIONAL POLICY ON INTERNATIONAL MIGRATION - K Karina; Maidah Purwanti (Polteknik Imigrasi, 2021)
This paper attemps to explain national policies that provide protection for refugees, human trafficking, and protection for foreign workers in an international context. Migration can occur because of the desire of the person or forced circumstances that make a person have to migrate. Migration is generally carried out by a person or group of people who want to get a more decent life by looking for a more decent job in another country. On the other hand, other factors cause disease, natural disasters, outbreaks of disease, and high crime rates in their home countries. Therefore, the role of the government through law enforcement officials and related public officials must coordinate well, firmly and fairly in enforcing the law. The results of this study indicate that the fact that the statement of the government in implementing its policies is that the government implements the policy is good or not. As smart as someone who makes policies, will always be smarter for someone who wants to violate the policy.